Personal history of diabetes as important as family history of colorectal cancer for risk of colorectal cancer: a nationwide cohort study - Khan, Uzair Ali; Fallah, Mahdi; Tian, Yu; Sundquist, Kristina; Sundquist, Jan; Brenner, Hermann; Kharazmi, Elham (The American journal of gastroenterology, 2020)
Diabetes mellitus (DM) and colorectal cancer (CRC) share some risk factors, including lifestyle and metabolic disturbances. We aimed to provide in-depth information on the association of CRC risk, especially early-onset CRC, with DM, family history of CRC, and age at DM diagnosis.